THE FORMATION OF A CONCEPTUAL AND CATEGORICAL APPARATUS FOR RESEARCH ON THE MANAGEMENT OF THE ECONOMIC SECURITY OF AGRARIAN ENTERPRISES - SENCHUK, Ihor; KUKHAR, Oleksandr; KATKOVA, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Initial conceptualization of economic security issues, its systematization, and logicization with the help of basic conceptual structures creates prerequisites for understanding the principles and methods of analysis of manifestations, resource base, and trends of economic security development. Within the framework of various economic paradigms, they are developing their approaches to the content and technology of the cognitive process, its capabilities, and reliability. Taking into account the geostrategic tasks of Ukraine, the experience of implementing the state food security strategy, it is essential to rethink the concept of Ukraine’s national interests in the economic sphere, assess new challenges and threats to economic security and, on this basis, prepare a new state strategy, as well as a mechanism for its implementation. The systems of economic activity, management, and compliance with the economic security of subjects of economic relations differ functionally and spatially. A significant part of economic phenomena, processes, several business entities, and economic relations are beyond the influence of the elements of the economic security system. All this actualizes the problem of analyzing information at the "output", primarily indicators of the effectiveness of the functioning of enterprises, organizations, individual industries, the quality and standard of living of employees, and the population as a whole, since these indicators act not only as indicators of social and economic well-being but also as criteria, by which it is possible to judge the level of internal threats to ensure sustainable and safe economic development. In the conditions of free market relations, the process of decentralizing the state management system in ensuring economic security, the role of economic managers of agro-industrial complex enterprises and organizations of all forms of ownership, vast and medium, is increasing. The content of this type of management, its functional, technological, and other features, is primarily determined by the state of the country’s economy and its industries as an object of management. Ensuring the economic security of enterprises in the agrarian sector of Ukraine depends on the constituent structures of the agricultural sector since the agrarian sector is closely connected with the entire agrarian complex of the country.